Prevalence and risk factors of angina pectoris and its association with coronary atherosclerosis in a general population, a cross-sectional study. (3rd October 2022) - Welen Schef, K; Hagstrom, E; Ravn-Fischer, A; Soderberg, S; Yndigegn, T; Tornvall, P; Jernberg, T
Abstract: Background: Angina pectoris (AP) is a common clinical presentation with low association to significant coronary artery disease (CAD) in selected cohorts, though yet associated with an elevated risk of major cardiovascular adverse events. Current knowledge on AP prevalence is not up to date since contemporary cross-sectional population-based studies using symptom evaluation are sparse and epidemiological studies often use administrative data from routine health care. Also, there is a lack of studies in the general population examining the association between AP and presence of coronary atherosclerosis. Purpose: To assess the prevalence of AP, the relationship to CAD, and risk factors associated to the conditions in a population-based, middle-aged Swedish cohort. Methods: Data were based on the Swedish CArdioPulmonary bioImage Study (SCAPIS), in which 30, 154 men and women aged 50–64 years were recruited from the general population between 2013 and 2018. Exposure variables included information from blood sampling, physiological examinations, coronary computed tomographic angiography (CCTA) and an extensive questionnaire, including WHO Rose questionnaire on AP. Participants that completed the Rose questionnaire were included and categorized as having Rose angina or No angina. Subjects with a valid CCTA were further assessed regarding correlation between having Rose angina and degree of CAD, categorized as obstructive (>50% occlusion, O-CAD), non-obstructive (<50% occlusion, NO-CAD) or normal coronary angiography (Normal CA). Associations between risk factor exposures and outcomes were analysed in both cohorts using bivariate logistic regression. Results: The main cohort consisted of N=28, 974 individuals, of which n=1025 fulfilled the criteria of Rose angina, giving a prevalence of 3.5%. Out of these, N=24, 602 subjects constituted the CCTA-cohort. Coronary atherosclerosis was significantly more common in individuals having Rose angina compared with those with No angina, (p≤0.001; O-CAD 11.8% vs 5.4%, NO-CAD 38.9% vs 37.0%, Normal CA 49.4% vs 57.7%). Factors associated with Rose angina were birthplace outside of Sweden, low educational level, unemployment, poor economic status, symptoms of depression, and high degree of general stress (Table). Physical inactivity, and current or previous cardiopulmonary diseases only marginally attenuated the associations. These findings were consistent in the sub-population of Rose angina with NO-CAD or Normal CA. Conclusion: Rose Questionnaire AP was common in a Swedish general population, with a greater association to coronary atherosclerosis at CCTA compared with asymptomatic individuals. O-CAD was though uncommon. Risk factors associated with AP were sociodemographic and psychological, irrespective of degree of CAD. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): SCAPIS has been funded mainly from the Swedish Heart- and Lung foundation and Knut och Alice Wallenberg foundation.